MEKANISME KOPING MAHASISWI KEPERAWATAN DALAM MENGHADAPI DISMENORE - -, Hartati; -, Munjiati; -, Khaerunisa (Jurnal Ilmiah Kesehatan Keperawatan, 2012)
Dysmenorrhea is menstrual pain before, during, and after menstruation. This pain happens along with nausea, headaches, feeling faint, and irritability it’s make women can’t work. Pain is a subjective feeling. People use various defense mechanisms and human adaptability varies. The purpose this research is to determine the coping mechanism student nursing in solving dysmenorrhea at program nursing of FKIK UNSOED Purwokerto. The research used descriptive qualitative with phenomenology approach. Purposive sampling methode was used to choose the participants and the data was analysed by interactive analysis model of Milles and Huberman. This research gave twelve themes which describe coping mechanism students nursing about the knowledge of dysmenorrhea sense, the knowledge about cause of dysmenorrehea, assumptions about dysmenorrhea, changes physical in the perceived, changes psychological in the perceived, changes activities in the perceived, knowledge of coping mechanisms for understanding, attitude in solving dysmenorrheal, behavior in solving dysmenorrheal, the factors of physical that affect the coping mechanism, the factors of psychological that affect the coping mechanism, and the factors of social support that affect the coping. Keywords : Coping mechanisms and dysmenorrhea